The Regularity of the Site of Impaction in Recurrent Gallstone Ileus: A Systematic Review and Meta-Analysis of Reported Cases. (2nd December 2021) - Alzerwi, Nasser A. N.; Idrees, Bandar; Alsareii, Saeed; Aldebasi, Yaser; Alsultan, Afnan
Abstract : Objective . Due to the rarity of recurrent gallstone ileus (RGSI), its epidemiological and clinical features are elusive. With a focus on mortality and the site of impaction, this study consolidates the key clinical characteristics of index GSI (IGSI) and RGSI. Methods . A meta-analysis of cases reported on RGSI was performed. Risk factors for mortality and site of impaction were examined, and a subgroup analysis was performed for age, sex, and site of impaction (jejunum, ileum, or others). Results . In the final analysis, 50 (56 individual cases) studies were included. The paired data for the site of impaction was available for 45 patients. Women accounted for 87.3% of all RGSI cases included in the pooled analysis. The median age (interquartile range, IQR) of the patients was 70 (63–76) years, and the median time of recurrence (IQR) was 20.5 (8.5–95.5) days. The overall mortality rate was 11.8%, without correlation between the mortality rate and age, the time of recurrence, or the site of impaction. The region in which the stone was found in RGSI and IGSI was similar in most cases p = 0.002 . Logistic regression also revealed a higher probability of stone impaction in the ileum in RGSI if it was the site of impaction in IGSI. In most cases, enterolithotomy was the preferred method. Conclusions . A high index of suspicion for RGSI should be maintained for older women with a history of GSI. The region where the stone was impacted during IGSI should be investigated first in such patients.